If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 13 = -99 + -9x Reorder the terms: 13 + 5x = -99 + -9x Solving 13 + 5x = -99 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 13 + 5x + 9x = -99 + -9x + 9x Combine like terms: 5x + 9x = 14x 13 + 14x = -99 + -9x + 9x Combine like terms: -9x + 9x = 0 13 + 14x = -99 + 0 13 + 14x = -99 Add '-13' to each side of the equation. 13 + -13 + 14x = -99 + -13 Combine like terms: 13 + -13 = 0 0 + 14x = -99 + -13 14x = -99 + -13 Combine like terms: -99 + -13 = -112 14x = -112 Divide each side by '14'. x = -8 Simplifying x = -8
| 6x-7y=3 | | 5-5y=-45 | | 2x(5x-4)=0 | | 8x^2+11x=0 | | 2x+30=9x-54 | | 5(3x+2)=4 | | -3(12+2x)=-20 | | (37b-4)-9(4b+3)=-6 | | 4x+-18=-14 | | 7x-(6x+4)=-2 | | 7x+5x+4+8=7x+4+4x | | 4(r+2)=16 | | 9(t-1)-7t+2=t-15 | | 81x^8y^4=0 | | -3y+2=-4y+6 | | 2y-4=5y-19 | | 4(d+1)=16 | | 7(x-1)=4[x-(3-x)] | | 4x+20=y | | 4m*-16m+12=0 | | -16t^2+32t+48=t | | 7x^2+9x+0=0 | | -16t^2+32t+48=x | | 3a^2+6a=0 | | 6x+61=12x+13 | | (x+1)*-15= | | 2n-1=11 | | -4a-3=7a-14 | | 100m+10=15 | | x^2=y-a | | (-3)+n=17 | | 5y-9y+2=-14+2+(-14) |